Monitoring oak processionary moth Thaumetopoea processionea L. using pheromone traps: the influence of pheromone lure source, trap design and height above the ground on capture rates. (15th February 2013) - Williams, David T.; Straw, N.; Townsend, M.; Wilkinson, A. S.; Mullins, A.
Abstract: A field trial conducted in the summer of 2011 evaluated three key parameters that might be influential for determining the number of adult male oak processionary moths (OPM) Thaumetopoea processionea (L.) caught in pheromone traps. Two types of traps (Delta and funnel; Oecos, U.K.) containing one of three different commercially available pheromone lures for OPM were placed out in the lower (3–5 m), mid (5–10 m) and upper (10–15 m) canopy of 72 individual oak trees in Richmond Park, in London, U.K. The traps were placed out for 8 weeks covering the main flight period of OPM, and significantly more male moths were captured in traps positioned in the upper canopy (76.6%) compared with either mid‐canopy (18.6%) or lower canopy (4.8%) positions. Funnel traps caught significantly more male OPM than Delta traps, catching almost six times as many moths over the trapping period. Traps containing one of the commercially available pheromone lures did not catch any moths, whereas traps with the other two lures caught similar numbers of moths. Chemical analysis revealed considerable differences between the three pheromone lures used in the trial in terms of the initial starting concentration of the primary component ( Z, Z )‐11, 13‐hexadecadienyl acetate and its dissipation over a 28‐day period. The results obtained in the present study indicate some of the main factors that need to be taken into account when using pheromone traps to monitor OPM populations and also contribute to the establishment of a standardized monitoring system for this recently established insect pest.